Cortical Excitability and Interhemispheric Connectivity in Early Relapsing–Remitting Multiple Sclerosis Studied With TMS-EEG - Zipser, Carl M.; Premoli, Isabella; Belardinelli, Paolo; Castellanos, Nazareth; Rivolta, Davide; Heidegger, Tonio; Müller-Dahlhaus, Florian; Ziemann, Ulf (Frontiers in Neuroscience, 2018)
Evoked potentials (EPs) are well established in clinical practice for diagnosis and prognosis in multiple sclerosis (MS). However, their value is limited to the assessment of their respective functional systems. Here, we used transcranial magnetic stimulation (TMS) combined with electroencephalography (TMS-EEG) to investigate cortical excitability and spatiotemporal dynamics of TMS-evoked neural activity in MS patients. Thirteen patients with early relapsing-remitting MS (RRMS) with a median expanded disability status scale (EDSS) of 1.0 (range 0 to 2.5) and 16 age- and gender-matched healthy controls (HC) received single-pulse TMS of left and right primary motor cortex (M1), respectively. Resting motor threshold (RMT) for left and right M1 was increased in MS patients. Latencies and amplitudes of N45, P70, N100, P180 and N280 TMS-evoked EEG potentials (TEPs) were not different between groups, except a significantly increased amplitude of the N280 TEP in the MS group, both for left and right M1 stimulation. Interhemispheric signal propagation (ISP), estimated from the area under the curve of TEPs in the non-stimulated vs. stimulated M1, also did not differ between groups. In summary, findings show that ISP and TEPs were preserved in early-stage RRMS, except for an exaggerated N280 amplitude. Our findings indicate that TMS-EEG is feasible in testing excitability and connectivity in cortical neural networks in MS patients, complementary to conventional evoked potentials. However, relevance and pathophysiological correlates of the enhanced N280 will need further study.